СТАВОВИТЕ НА ИДНИТЕ НАСТАВНИЦИ ПО АНГЛИСКИ ЈАЗИК КОН ИМПЛЕМЕНТИРАЊЕ НА АВТОНОМНОТО УЧЕЊЕ - Николовска Анжела (Филолошки факултет „Блаже Конески“, 2019)
The study presents the results of a survey conducted among third and fourth-year students at the English Department, Blaže Koneski Faculty of Philology. It casts light on pre-service teachers’ beliefs about the classroom implementation of learner autonomy. The findings reveal that the trainees strongly support the engagement of the learner in establishing the course objectives and content, selecting certain types of materials, determining the pace of the lesson, the classroom activities, the quantity and type of homework, what is to be learned from the materials, the learning procedures and self-assessment. Finally, the possible reasons for such strong support are discussed as well as the research implications.
Keywords: pre-service teacher training, survey, beliefs, learner autonomy, teacher autonomy